Answer:
B) 53x + 74
Step-by-step explanation:
(59x + 64) - (6x - 10) = 59x + 64 - 6x + 10
= 53x + 74
Answer:
First option: 3 blocks to the right, 5 blocks down
Step-by-step explanation:
1.They basically all did one big bug,not separate hugs with different bears.
Answer:
The answer to your question is the letter a.
Step-by-step explanation:
Data
x² + 12x + c
If this trinomial is a perfect square trinomial, the third term must be half the second term divided by the square root of the first term, and to the second power.
-Get half the second term
12x/2 = 6x
-Divide by the square root of the first term
6x/x = 6
-Express the result to the second power
6² = 36
-Write the perfect square trinomial
(x² + 12x + 36) = (x + 6)²
Answer:
1. x^4 -x^3 -4x^2 -3
a1 = -7.4
an = an-1 -13.8 (choice 1)
Step-by-step explanation:
f(x) = x^4 -x^2 +9
g(x) = x^3 +3x^2 +12
We are subtracting
f(x) -g(x) =x^4 -x^2 +9 - ( x^3 +3x^2 +12)
Distribute the minus sign
x^4 -x^2 +9 - x^3 -3x^2 -12
I like to line them up vertically
x^4 -x^2 +9
- x^3 -3x^2 -12
-------------------------
x^4 -x^3 -4x^2 -3
2. a1 = -7.4
To find the common difference, take term 2 and subtract term 1
-21.2 - (-7.4)
-21.2 + 7.4
-13.8
an = an-1 -13.8